New ways in which the United Nations could address the crisis of multilateralism and trade and its development machinery, as well as what the contribution would be (UN New YorkUS, 2018)
Positis that the challenges for the international community is to ensure that the headwinds that multilateralism and international trade are currently facing do not hold back the contribution of international trade to the achievement of the 2030 Agenda for Sustainable Development and the Sustainable Development Goals.
Keywords: INTERNATIONAL TRADE